Consumer Dispute Resolution By BPSK In Protecting Consumer Rights - Abdul Samad (International Asia Of Law and Money Laundering (IAML), 2022)
In Law No. 8 of 1999 on Consumer Protection which aims to protect the rights of consumers. The Consumer Dispute Resolution agency (BPSK) is an alternative dispute resolution institution whose existence is to resolve consumer dispute problems. In Medan City as an urban area with the majority of urban communities, there is a potential for Consumer Dispute problems. BPSK established in the region of Regency/city in Indonesia based on the mandate of Law No. 8 of 1999 on Consumer Protection. Then strengthened by Government Regulation No. 58 of 2001 on guidance and supervision of the implementation of Consumer Protection, Presidential Decree No.38 of 2012 on the establishment of the Dispute Resolution agency . This study aims to identify the position of BPSK in Medan dispute resolution system based on positive law applicable in Indonesia in its efforts to protect the rights of consumers in the city of Medan and its challenges.